2021
DOI: 10.2147/copd.s291477
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Airflow Limitation and Carotid Intima-Media Thickness in the Japanese Population

Abstract: Purpose This study aimed to reveal the association between airflow limitation (AL) and carotid intima-media thickness (IMT) according to smoking status in Japan. Subjects and Methods This cross-sectional study was performed in 2809 subjects, who underwent a comprehensive health examination with pulmonary function tests and carotid ultrasonographic measurement. AL was defined as forced expiratory volume in 1 s/forced vital capacity of <0.7. The subjects were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Patients with COPD have also higher risk for increased cIMT than healthy subjects. In this regard, Watanabe et al ( 33 ) have recently demonstrated the association between cIMT and forced expiratory volume (FEV) below 70% and smoking experience. On the other hand, mechanisms underlying subclinical organ damage in the obstructive sleep apnea (OSA) setting are multifactorial, including endothelial dysfunction, hypertension, and vascular remodeling (also comprehending increased cIMT) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with COPD have also higher risk for increased cIMT than healthy subjects. In this regard, Watanabe et al ( 33 ) have recently demonstrated the association between cIMT and forced expiratory volume (FEV) below 70% and smoking experience. On the other hand, mechanisms underlying subclinical organ damage in the obstructive sleep apnea (OSA) setting are multifactorial, including endothelial dysfunction, hypertension, and vascular remodeling (also comprehending increased cIMT) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%